Efektivitas Model Pembelajaran Blended Learning Dalam Meningkatkan Hasil Belajar Siswa Pada Materi Asam Basa Di SMA Negeri 1 Ratahan - Efraim M Talenggoran; Marlin Karundeng (Chemistry Department, Universitas Negeri Manado, 2021)
This study aims to determine the efectiveness of the Blended Learning learning model on student learning outcomes on acid-base material. This research was conducted at SMA Negeri 1 Ratahan in the 2020/2021 academic year. The research method used is descriptive qualitative. A total of 18 student of class XI MIA 1 were selected to be set as research samples. The research data was obtained from the final evaluation in the form of multiple choice questions and student response questionnaires. Based on the data analysis, the percentage of student learning completeness was 83.3% with a very good category. The responses given by students to the Blended Learning learning questionnaire were 92.2% and the results of the N-Gain Test showed that the effectiveness of using the learning model was 0.744 with a high category. Based on the resuts of this study, it can be concluded that blended learning model is effective in improving student learning outcomes on acid-base material.